Penerapan IoT untuk Kota Cerdas - Yoni Marine; Saluky Saluky (ITEJ (Information Technology Engineering Journals), 2018)
The Internet of Things (IoT) should be able to handle heterogeneous systems in a transparent and stable manner by providing open access to the selected data subset for the development of a large number of digital services. Building a common architecture for IoT is a very complex task, mainly because of the huge variety of devices, different technologies and services required. In this paper, we focus exclusively on large urban IoT systems. IoT's development is designed to support smart city’s vision to utilize the most advanced communications technologies to support value-added services for city administration and for citizens. The paper provides a comprehensive survey of technologies, protocols, and architectures that allow for urban IoT.